Statistični nadzor procesa: Praktikum (navodila za vaje pri predmetu Metode eksperimentalnega dela), 2nd editon - Črepinšek Lipuš, Lucija (2023)
Statistical Process Control: Practicum (Instructions for Exercises in the Subject Methods of Experimental Work). The practicum Statistical Process Control is a study aid for conducting exercises in the subject Methods of experimental work. Descriptions of basic quality management tools are followed by examples and work tasks with procedures based on the principles of statistical product quality control. The tasks include measuring samples and evaluating the results in the Excel program and with QI Macros tool.Second edition.E-book available only for students of the University of Maribor, Faculty of Mechanical Engineering.
Keywords: quality assurance; statistical process control; process capability; histogram; control chart